(untitled) (Journal of Entrepreneurship and Business, 2024)
This study investigates the factors influencing e-commerce adoption among SMEs in Sabah and Sarawak, addressing gaps in the existing consensus and theoretical framework. Utilizing the Technology-Organisation-Environment theory, the research focuses on perceived usefulness, perceived ease of use, organizational readiness, and top management support, with government support as a moderating variable. Employing a quantitative approach and survey methodology, data analysis was conducted using SPSS and SmartPLS 4. The results reveal that perceived usefulness and ease of use positively impact e-commerce adoption, and government support moderates the relationship between ease of use and adoption. The findings highlight the crucial role of the technological context, particularly user experience. The study underscores that user-friendly and useful e-commerce platforms increase the likelihood of adoption, while government support is vital through regulations and infrastructure improvements. Future research is recommended to explore e-commerce adoption across diverse industries and examine post-adoption stages to identify evolving patterns over time.